Masalah Tenaga Kerja Indonesia di Arab Saudi dan Perjuangan Diplomasi Republik Indonesia - Nurnaningsih Al Hasmi; Burhanuddin; Patrice Lumumba (Hasanuddin Journal of International Affairs, 2022)
This research is intended to determine the basis of the diplomatic struggle of the Republic of Indonesia in the problem of TKI in Saudi Arabia and the substance of the diplomatic struggle of the Republic of Indonesia against the problem of TKI in Saudi Arabia. The results of the study indicate that the The large number of migrant workers to Saudi Arabia is due to the high demand from the country as a developed country which continues to develop its country in various sectors, thus requiring a lot of manpower. This is an opportunity for the Government of Indonesia to send TKI to Saudi Arabia in order to reduce unemployment and improve the economy of the people in Indonesia, but the consequences of this delivery cause various problems such as: persecution, unpaid salaries, harassment, and murder which cause problems in the context of Indonesia-Saudi Arabia relations. On that basis, as a consequence, the Indonesian Government must fight for the fate of the TKI through diplomacy such as mediating the interests of the TKI with the Government of Saudi Arabia, providing advocacy or legal assistance.   Penelitian ini bertujuan untuk mengetahui dasar perjuangan diplomasi Republik Indonesia dalam permasalahan TKI di Arab Saudi dan substansi perjuangan diplomasi Republik Indonesia terhadap permasalahan TKI di Arab Saudi. Hasil penelitian menunjukkan bahwa Banyaknya TKI ke Arab Saudi disebabkan oleh tingginya permintaan dari negara tersebut selaku negara maju yang terus membangun negaranya di berbagai sektor, sehingga membutuhkan banyak tenaga kerja. Hal ini menjadi peluang bagi Pemerintah Indonesia untuk mengirimkan TKI ke Arab Saudi agar dapat mengurangi pengangguran dan meningatkan ekonomi masyarat di Indonesia, akan tetapi akibat dari pengiriman tersebut menimbulkan berbagai permasalahan seperti: penganiayaan, gaji tidak dibayar, pelecehan, dan pembuhunan yang menimbulkan masalah dalam konteks hubungan Indonesia-Arab Saudi. Dengan dasar itu, sebagai konsekuensi bagi Pemerintah Indonesia harus memperjuangkan nasib para TKI tersebut melalui diplomasinya seperti memediasi kepentingan para TKI dengan Pemerintah Arab Saudi, memberi advokasi atau bantuan hukum.